A biallelic truncating AEBP1 variant causes connective tissue disorder in two siblings. Issue 1 (11th December 2018) - Hebebrand, Moritz; Vasileiou, Georgia; Krumbiegel, Mandy; Kraus, Cornelia; Uebe, Steffen; Ekici, Arif B.; Thiel, Christian T.; Reis, André; Popp, Bernt
Abstract : Biallelic variants in the AEBP1 gene cause a novel autosomal‐recessive connective tissue disorder (CTD) reminiscent of Ehlers‐Danlos Syndrome (EDS). The four previously reported individuals show considerable clinical variability. Unbiased high‐throughput sequencing enables the rapid identification of additional cases for such rare entities. We identified the homozygous nonsense variant c.917dup, p.Tyr306* in AEBP1 using clinical exome sequencing in a female individual with previously unsolved CTD. Segregation testing confirmed homozygosity in the clinically affected brother and heterozygous carrier status in the healthy mother. Chromosomal microarray showed that the variant lies in a run of homozygosity, suggesting a common origin of this genomic segment. RT‐PCR analysis in the mother revealed a monoallelic expression of the normal transcript supporting a nonsense‐mediated mRNA decay and functional nullizygosity as disease mechanism. We describe two individuals from a fourth family with AEBP1 ‐associated CTD. Our results further verify that autosomal‐recessive inherited LOF variants in the AEBP1 gene cause clinical features of different EDS subtypes, but also of the marfanoid spectrum. As identification of further individuals is necessary to inform the clinical characterization, we stress the added value of exome sequencing for such rare diseases.